Investigation of Cycling Performance in a Solid-State Fluoride-Ion Battery Based on Copper Fluoride Electrodes - Chien-Hung Chen; Ching-Tsung Yu; Yu-Fei Chang (International Journal of Engineering and Technology Innovation, 2024)
This study investigates the performance and cycling fading of a solid-state fluoride-ion battery (FIB) based on the CuF2 electrode. The cathode and solid electrolyte of CuF2 composite and La0.9Ba0.1F2.9 are prepared by ball-milling. Meanwhile, the anode materials are used as Sn and Pb. All FIB cells with sandwich structures are fabricated by compressing under a pressure of 4.5 tons/cm2. Electrochemical measurements of discharge/charge are performed at 423 K and under 40 μA/cm2. The resultant cycling stability of the cell with the Pb anode is higher than that of the cell with the Sn anode. Concerning the cell with Pb anode, the first and tenth discharge capacities of 150 and 90 mAh/g are obtained. X-ray photoelectron analysis demonstrates that the cycling fading of the cell with the Sn (or Pb) anode may be attributed to the irreversible formation of materials (e.g., SnF4 or PbF4) during the electrochemical reaction.